PENGARUH METODE LATIHAN POWER TERHADAP KECEPATAN TENDANGAN DOLLYO CHAGI PADA ANGGOTA TAEKWONDO SIPJIN KABUPATEN SUKABUMI TAHUN 2019 - Hamad Fauzi; Firman Septiadi; Firman Maulana (Indonesia Sport Journal, 2019)
This study aims to determine the effect of power training on the speed of the Dolly Chagi kick in the Sipjin taekwondo member Sukabumi Regency. The importance of the role of the power training method to the speed of the Dolly Chagi kick in taekwondo kicks. This research uses quantitative methods (pre-experimental, pretest-posttest control group design). This study population is a member of the Sipab taekwondo Sukabumi Regency, a population of 25 people taken by 20 people. The sample of this study was all members of taekwondo with purposive sampling technique, which is the technique of determining the sample with certain considerations. The instruments used in this study include: (1) training program, (2) dollyo chagi kick speed test. Based on the results of calculations using the normality test, F-test and T-test analysis techniques. the F count result is greater than the F table, i.e. F count (2.39) and F table (2.98). and T arithmetic greater than T table that is T arithmetic (2,934) and T table (1,812). based on a significance level of 0.05, Ha was accepted, meaning that there was an influence of the power training method on the speed of the Dolly Chagi kick on members of the Sipjin Taekwondo Sukabumi Regency in 2019